Clinical evaluation of a novel fixed-dose combination tablet (Sentorpil® ForteGold) versus compounded powdered medications in dogs with myxomatous mitral valve disease: a randomized, double-blind study - Park, Jiyoung; Lee, Jiyoon; Lee, Sang-Joon; Hyun, Changbaig (Frontiers in Veterinary Science, 2025)
IntroductionMyxomatous mitral valve disease (MMVD) is a prevalent cardiac condition in older, small-breed dogs, often managed with multiple medications. Traditional administration involves compounded powdered mixtures, which may lead to dosing inaccuracies and reduced compliance.MethodsIn a randomized, double-blind clinical trial, 60 client-owned dogs diagnosed with ACVIM stage C MMVD were assigned to receive either a novel fixed-dose combination tablet (Sentorpil® ForteGold) or a compounded powdered mixture of torsemide, pimobendan, enalapril, and spironolactone. Treatments were administered twice daily over 56 days. Clinical signs, blood chemistry, electrolyte levels, thoracic radiography, echocardiography, and biomarkers (NT-proBNP, SDMA, and cPL) were evaluated at baseline and on days 7, 14, 28, and 56.ResultsBoth groups exhibited significant improvements in clinical signs, including exercise intolerance, appetite, respiratory effort, and coughing, with the ForteGold group showing earlier and more sustained responses. Blood chemistry and electrolyte levels remained within normal ranges, indicating a favorable safety profile. Radiographic assessments revealed a gradual decrease in vertebral heart score and normalization of lung fields by Day 56 in both groups. Echocardiographic parameters (LA/Ao, LVIDd/Ao, MVE) improved significantly, with the ForteGold group demonstrating earlier enhancements. NT-proBNP levels decreased in both groups, with a more pronounced reduction in the ForteGold group. No significant changes were observed in SDMA and cPL levels, suggesting stable renal and pancreatic functions.DiscussionThe fixed-dose combination tablet (Sentorpil® ForteGold) offers a clinically effective and safer alternative to compounded powdered medications for managing MMVD in dogs. Its formulation ensures accurate dosing, improved owner compliance, and enhanced clinical outcomes. Further studies with larger populations and extended follow-up periods are warranted to confirm these findings.